Milk analysis using milk analyzers in a standardized setting (MAMAS) study: A multicentre quality initiative. Issue 7 (July 2020) - ,; Kwan, C.; Fusch, G.; Rochow, N.; el-Helou, S.; Belfort, M.; Festival, J.; Hair, A.; Hascoet, J.-M.; Kuehn, T.; MIRIS,; Nelle, M.; et al.
Summary: Background: Human milk analyzers are increasingly used to rapidly measure the macronutrient content in breast milk for individual target fortification, to reduce the risk of postnatal growth restriction. However, many milk analyzers are used without calibration, validation or quality assurance. Aims: To investigate measurement quality between different human milk analyzers, to test whether accuracy and precision of devices can be improved by establishing individual calibration curves, and to assess long-term stability of measurements, following good clinical laboratory practice (GCLP). Methods: Sets of identical breast milk samples were sent to 13 participating centres in North America and Europe, for a total of 15 devices. The study included 3 sets of samples: A) initial assessment of the device's performance consisting of 10 calibration samples with random replicates; B) long term stability and quality control consisting of 2 batches of samples to be measured every time before the device is used, over 6 months; C) ring trial consisting of 2 samples to be measured monthly. The devices tested were Unity SpectraStar (n = 5) and MIRIS Human Milk Analyzer (n = 10). Results: There are significant variations in accuracy and precision between different milk analyzers' fat, protein and lactose measurements. However, the accuracy of measurements can be improved by establishing individual correction algorithms. Repeated measurements are more robust when coming from a larger batch volume. Long term stability also varies between devices. Conclusion: The variations in measurements between devices are clinically significant and would impact both daily dietary prescriptions, and the outcomes of clinical studies assessing the effect of targeted adjustment of nutrient intake in preterm babies. This study shows that it is crucial to follow GCLP when using milk analyzers to ensure proper measurement of macronutrients, similar to what is required of other medical devices.